The Role of Dental Hygienist in the Implementation of A Program for the Prevention of Dental Diseases in Preschool Institutions - Turavi Dilnoza Jo’rabek; Rakhimberdiev Rustam Abdunosirovich (Zien Journals, 2022)
This article about children is more prone to dental health than adults. The remains formed after eating food on the teeth are the main factor of the formation of caries. Therefore, caries in children and adolescents are more than. This is an painless procedure, since there is no abrasion on the teeth and children, it is possible to slow down the caries more easily with the help of this method of treatment. It is then an important treatment option for the healthy formation of permanent teeth
Keywords: teeth and children; dental diseases is one of the effective; healthy lifestyle in medicine and in particular the development